(untitled) - Futrell, Charles (Boston, Mass., 2006)
"Fundamentals of Selling: Customers For Life Through Service, 9/e", is one of McGraw-Hill's best-selling texts in the Selling discipline. Its approach is classic and practical and emphasizes role-plays. "Fundamentals", written by a salesperson turned teacher, draws widely from Charles Futrell's experience as a sales professional rather than from a staid theoretical perspective. The text is filled with practical tips and business-examples gleaned from years of experience in sales with Colgate, Upjohn, and Ayerst and from the author's sales consulting business. Charles Futrell focuses on improving communication skills and emphasizes that no matter what career a student pursues; selling skills are a valuable asset.
Keywords: Selling